Physical factors and motivation in learning Dollyo Chagi kicks: a narrative review - Popo Hartono; Muhamad Sazeli Rifki; Syahrial Bakhtiar; Ardo Okilanda (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
Technical mastery of the Dollyo Chagi kick in martial arts learning is not solely determined by isolated physical abilities but emerges from the interaction of physical and psychological factors. Previous studies have predominantly examined flexibility, explosive power, and motivation separately, resulting in fragmented understanding of their combined role in technical skill development. This narrative review aims to synthesize and conceptualize the interrelated contributions of flexibility, lower-limb explosive power, and motivation in learning and executing the Dollyo Chagi kick. A qualitative narrative synthesis was conducted on peer-reviewed national and international literature published between 2018 and 2025, selected through purposive sampling. The findings indicate that flexibility functions as a biomechanical prerequisite enabling effective movement range and technical control, while explosive power acts as a performance amplifier that enhances kick speed and force when technical foundations are established. Motivation emerges as a psychological mediator that sustains training engagement and supports consistent skill acquisition. This review highlights the need for an integrated training and pedagogical approach, providing a conceptual framework to inform future empirical research and evidence-based coaching in martial arts education.